The future of Philippine organic produce a foresight analysis through scenario building - Invierno, Ian Junelord Columna; Imbang, Prof. Glen A. (Quezon City University of the Philippines Diliman, 2015)
The objective of this paper is to carry out a foresight analysis of the Philippine organic fresh produce industry by the year 2025. Scenario planning was the methodology used to build the various scenarios. Literature reviews, surveys, and field expert interviews were conducted to scan the current status of Philippine organic agriculture in order to determine predictable variables and key driving forces. Four scenarios were developed characterizing possible future states of the local organic market. Future possible states described were slow continued demand growth, transformational growth in both global and local trade, decline in supply and demand, and rapid farmer conversion rate to organic farming system. The scenarios were then assessed for their implication to the strategic planning in the market adoption of the Philippine organic produce. Strategies for businesses were proposed.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Organic farming -- Philippines; Foresight analysis; Scenario building